Kajian Sifat Fisika Tanah Pada Perkebunan Kelapa Sawit (Elaeis guineensis Jacq) di Kecamatan Tambang, Kampar - Sari, Via Permata; trizayuni, Riskia; Zafitra, Zafitra (Soilrens, 2026)
This study aims to identify and analyze the physical properties of soils in oil palm plantation areas in Tambang District, Kampar Regency. Soil sampling was conducted purposively at depths of 0–30 cm and 30–60 cm, and the samples were analyzed in the laboratory for parameters including permeability, moisture content, bulk density (BD), particle density (PD), total pore space (TPS), organic carbon (C-organic), and organic matter. The results showed soil permeability at the 0–30 cm depth was classified as slow (0.47 cm·hour⁻¹), while at the 30–60 cm depth it was moderately slow (1.026 cm·hour⁻¹). Moisture content decreased from 17.63% in the upper layer to 10.14% in the lower layer. BD and PD values were very low, at 0.2171 g·cm⁻³ and 0.6391 g·cm⁻³ in the upper layer, and 0.1382 g·cm⁻³ and 0.5428 g·cm⁻³ in the lower layer. Total pore space was extremely high, at 66.04% and 74.54%, respectively. Organic carbon and organic matter contents were classified as very high at both depths, with values ranging from 56.77% to 57.1% and 97.8% to 98.44%, respectively. The high organic matter content results in low bulk density, high porosity, and substantial water holding capacity; however, the dominance of macropores in the lower layer leads to relatively lower moisture content. These conditions reflect the characteristics of peat soils, which are highly porous but require proper water and nutrient management to optimize oil palm productivity.